Kriteria Perbuatan Tercela dalam Pemberhentian Kepala Daerah di Indonesia Setelah Putusan Mahkamah Konstitusi Nomor 2/PUU-XX/2022 - Keshia Monika Prianto; Tomy Michael (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study examines the criteria of disgraceful conduct in the dismissal mechanism of regional heads in Indonesia following Constitutional Court Decision No. 2/PUU-XX/2022. The decision underscores the necessity of a constitutional interpretation of the requirement “never having committed disgraceful conduct” in order to prevent abuse of power and political injustice in regional governance. Employing a normative legal research method, this study analyzes primary legal materials, including Constitutional Court decisions and statutory regulations, as well as secondary legal literature. The findings reveal that the notion of disgraceful conduct had previously functioned as a vague norm, enabling subjective and politically motivated interpretations, particularly by regional legislative bodies. The Constitutional Court, through its decision, transformed this open norm into a more limitative and objective standard by specifying concrete forms of conduct, such as gambling, intoxication, drug abuse, adultery, and other serious violations of decency. Furthermore, the Court emphasized that allegations of disgraceful conduct must be supported by clear, lawful, and verifiable evidence, in line with the principles of due process of law. This reformulation strengthens legal certainty, protects the political rights of elected regional heads, and preserves the stability of local governance. The study recommends legislative synchronization through amendments to the Regional Government Law and the issuance of judicial guidelines to ensure uniform standards of proof in dismissal proceedings, thereby reinforcing constitutional justice and the rule of law in Indonesia.